Variation of CO2 adsorption in isostructural Cd(II)/Co(II) based MOFs by anion modulation - Singh, Udai P.; Narang, Shikha; Pachfule, Pradip; Banerjee, Rahul (CrystEngComm, 2014)
{A potential multidentate tris-pyridyl ligand has been synthesized, and later employed for the tailoring of four isostructural cadmium(II)/cobalt(II) two dimensional (2D) metal organic frameworks, [[ M(dmpt)(2)(X)(2)].xS](n), where S = solvent

Construction and structural diversity of Cd-MOFs with pyrazole based flexible ligands and positional isomer of naphthalenedisulfonate - Singh, Udai P.; Singh, Neetu; Chandra, Suman (Inorganic Chemistry Communications, 2015)
In the present communication, we have reported the construction of a series of Cd(II)-MOFs using conformationally flexible ligand (CFL); 3,3',5,5'-tetramethy1-4,4'-bipyrazolyl (H(2)BPz), flexible bent ligand (FBL); methylenebis-(3,5-dimethylpyrazole) (H(2)MBPz) and positional isomer of naphthalene disulfonic acid salt ligands (1,5-NDS, 2,6-NDS). By using these ligands, four new coordination polymers namely [Cd(H(2)MBPz)(2) center dot 1,5-NDSA](n) (NDS-MOF-1), [Cd(H(2)BPz)center dot 1,5-NDSA](n) (NDS-MOF-2), {[Cd(H(2)MBPz)(2)](2+)center dot 2,6-NDSA(2-)}(n), (NDS-MOF-3) and {[Cd(H(2)BPz)(2)](2+).2,6-NDSA(n)(2-}) (NDS-MOF-4) have been synthesized. The crystal structure analysis revealed that the employment of positional isomeric naphthalene disulfonic acid salts resulted in different architectures ranging from one dimensional chain to two dimensional grid network and further connected into a three dimensional supramolecular structure through intermolecular hydrogen bonds, pi center dot center dot center dot pi and C-H center dot center dot center dot pi interactions. In addition, the photophysical properties and thermal stability studies for all the NDS-M0F5 1-4 were also investigated. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Cadmium(II); Conformation; coordination polymers; Naphthalenedisulfonate; Photophysical properties; thermal stability